How Important is the Global Financial Cycle? : Evidence from Capital Flows - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2017)
This study quantifies the importance of a Global Financial Cycle (GFCy) for capital flows. We use capital flow data dis-aggregated by direction and type between 1990Q1 and 2015Q5 for 85 countries, and conventional techniques, models and metrics. Since the GFCy is an unobservable concept, we use two methods to represent it: directly observable variables in center economies often linked to it, such as the VIX; and indirect manifestations, proxied by common dynamic factors extracted from actual capital flows. Our evidence seems mostly inconsistent with a significant and conspicuous GFCy; both methods combined rarely explain more than a quarter of the variation in capital flows. Succinctly, most variation in capital flows does not seem to be the result of common shocks nor stem from observables in a central country like the United States.